Cannabis-Based Medicinal Products in the Treatment of Post-Traumatic Stress Disorder in Children and Young People: A Literature Review - Qudus Lawal; Shatha Shibib; Adeola Animashaun (BJPsych Open)
Aims: Post-traumatic stress disorder (PTSD) is a condition that may develop following exposure to a highly threatening or horrific event or series of events. PTSD can affect people across all age groups with extensive impact on functioning and is often associated with psychoactive substance misuse. Cannabis is one of the most abused psychoactive substances worldwide, with users reporting anxiolytic benefits. Cannabis-based medicinal products (CBMPs) have gained more attention and interest over the past few years due to changes in the legislation around cannabis worldwide. Research has shown cannabis-based medicinal products to be effective in treating several medical conditions. Observational studies in adult populations indicate some therapeutic promise for CBMPs in PTSD, but these results are not generalizable to younger populations.